Serine-Threonine Kinase Receptor-associated Protein Inhibits Apoptosis Signal-regulating Kinase 1 Function through Direct Interaction - Jung, Haiyoung (American Society for Biochemistry and Molecular Biology, 2010)
Serine-threonine kinase receptor-associated protein (STRAP) interacts with transforming growth factor β (TGF-β) receptors and inhibits TGF-β signaling. Here, we identify STRAP as an interacting partner of ASK1 (apoptosis signal-regulating kinase 1). The association between ASK1 and STRAP is mediated through the C-terminal domain of ASK1 and the fourth and sixth WD40 repeats of STRAP. Using cysteine-to-serine amino acid substitution mutants of ASK1 (C1005S, C1351S, C1360S, and C1351S/C1360S) and STRAP (C152S, C270S, and C152S/C270S), we demonstrated that Cys(1351) and Cys(1360) of ASK1 and Cys(152) and Cys(270) of STRAP are required for ASK1-STRAP binding. ASK1 phosphorylated STRAP at Thr(175) and Ser(179), suggesting a potential role for STRAP phosphorylation in ASK1 activity regulation. Expression of wild-type STRAP, but not STRAP mutants (C152S/C270S and T175A/S179A), inhibited ASK1-mediated signaling to both JNK and p38 kinases by stabilizing complex formation between ASK1 and its negative regulators, thioredoxin and 14-3-3, or decreasing complex formation between ASK1 and its substrate MKK3. In addition, STRAP suppressed H(2)O(2)-mediated apoptosis in a dose-dependent manner by inhibiting ASK1 activity through direct interaction. These results suggest that STRAP can act as a negative regulator of ASK1.